Synthesis of cholest-5-en-3-ol(3β)-3-[4-(2,2,2-trifluoroacetamido) benzoate] (ChTfAB) a thermotropic liquid crystalline material (Indian Journal of Chemistry (IJC), 2023)
The synthesis of cholest-5-en-3-ol(3β)-3-[4-(2,2,2-trifluoroacetamido)benzoate] (ChTfAB) is carried out by esterification of cholesterol and p-nitrobenzoic acid using DCC, DMAP, followed by reduction of nitro group using SnCl2. The so formed amino group is further N-acylated using trifluoroacetic anhydride. The newly synthesized compound is characterized using IR and 1H NMR spectroscopic techniques. Its mesomorphic properties have been investigated using Differential Scanning Colorimetry (DSC) and Polarising Optical Microscopy (POM). The thermal and phase behaviour studies reveal the synthesized compound to be an enantiotropic, thermotropic liquid crystal. This synthesized compound overcomes the problem of degrading at the melting temperature associated with one of the previously synthesized and reported steroidal compound.